Faktor-Faktor yang Berhubungan dengan Penggunaan Alat Kontrsepsi Suntik 3 Bulan di PMB Villy Agustin Palembang Tahun 2021 - Elsi Wulandari; Chairuna Chairuna; Erma Puspitasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
WHO explained that the increase in contraceptive use was highest in Asia and Latin America, and the lowest in Sub-Saharan Africa. Injec Tabel contraception is in great demand because it is a good alternative for contraception for women who want long-term and effective contraception. A person's decision to choose contraceptives is influenced by age, education, knowledge, parity, income. The purpose of the study was to determine the relationship between age, education, and parity with the use of 3-month injec Tabel contraceptives at PMB Villy Agustin Palembang in 2021. Analytical Survey Research with a Cross Sectional approach. The population is all active family planning acceptors who come to PMB Villy Agustin Palembang, namely 283 mothers, and 74 samples taken using the Slovin formula and simple random sampling technique. The secondary data used were processed and analyzed by univariate and bivariate analysis with the Chi-Square test. The results showed that there was a relationship between age (P-value = 0.037), education (P-value = 0.002) and parity (P-value = 0.034) with the use of 3-month injec Tabel contraceptives at PMB Villy Agustin Palembang in 2021. In conclusion, there was a relationship between age, education and parity with the use of 3-month injec Tabel contraceptive device at PMB Villy Agustin Palembang in 2021. It is hoped that health workers will be able to improve the quality of health services and public knowledge about all contraception so that they can increase the use of appropriate contraceptives in EFA.